KONSEP DIRI, PEER GROUP, DAN KECENDERUNGAN MENJADI KORBAN KEKERASAN DALAM PACARAN - Hanoum, Magdalena; Muslimah, Alfiana Indah (SOUL : Jurnal Pemikiran dan Penelitian Psikologi, 2017)
This study aims to analyze correlation as well as the influence of self concept and peer group on potential tendency/potentials to be dating violence victims in late adolescene (early adulthood). The study population is the late adolescent/adult at two private universities in the city of Bekasi. The sample size is 172 male and female students aged 18-21 years. Data were collected using three measuring instruments; self-concept scale, peer group scale and scale Tendency to be a victim of dating violence (Conflict of Adolescent Dating Relationship Inventory). Analysis of individual characteristics, self-concept, peer group and its relation to the tendency to become victims of dating violence, processed and analyzed by using descriptive analysis. Interconnection test and the influence of independent variable (self concept and peer group) partially or collectively to the dependent variable (tendency to become dating violence victim) using multiple linear regression test. The results show that the Self Concept correlates and influences the tendency of becoming a victim of dating violence, in the opposite relationship. This means that the higher the self concept of the subject then the tendency to become victims of dating violence is lower. These relationships and influences are statistically significant. The peer group relates and influences the tendency of becoming a dating violence victim in the opposite direction. This means that the higher the peer group (the ability to not be affected by the peer group / ability to think and act independently), the lower of the tendency to become victims of dating violence. However, the relationship and influence of peer groups on the tendency to become victims of dating violence is not statistically significant